Museum specimens and occurrences of Glottidia audebarti, Discradisca strigata and other brachiopods (Brachiopoda) in the Pacific of Costa Rica - José A. Vargas Zamora; Rita Vargas-Castillo (Cuadernos de investigación UNED, 2023)
Introduction: Lamp shells or brachiopods have a rich fossil record but only about 400 extant species. Their diversity on the Eastern Pacific is poorly known and only eight species are reported for the Pacific of Costa Rica. Objective: To list the specimens from Costa Rica and provide a distribution map along its Pacific coast. Methods: We checked collections at the University of Costa Rica (MZ-UCR) and Scripps Institution of Oceanography. Results: We found 22 records at MZ-UCR and 10 at Scripps, both include unidentified specimens, as well as Glottidia audebarti and Discradisca strigata, which are frequently collected intertidally. Conclusion: The study of Eastern Pacific living brachiopods is at an early stage; ecological studies could focus on the more easily accessed intertidal species.